(3MGTjI Ydi dhGeY GdCSQGQ aj TQM eWGdY GdCfhGQs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; MGeOG GdajGV GdMcje TGcQG GdhgGH GdbOje bhdg GdajGV GdhgGH jQjO Cfg jecf Med daX GdajGV Ydi eYfi GdhgGH aj YHGQI GdTGQM Ydi hLgjfs
(3BNQgG (B:s
(3deG cGf GdSDGd Ydi GdhLg GdPj CXgQ JhLjgGJ ceG Med dge YHGQI GdSDGd Ydjg hGdYHGQI GdSDGd eMJed KGdK SfPcQg Ef TGA Gddg JYGdis
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs